Epidemiological description of burn cases reported in the state of Sergipe during the period from 2019 to 2023 (Research, Society and Development, 2024)
Introduction: Burns vary in severity, ranging from minor irritations to life-threatening injuries. The consequences of burns are multifaceted, encompassing physical, emotional, and economic impacts. In Brazil, about 1 million people suffer burns annually, with 100,000 seeking hospital care and approximately 2,500 dying from complications. Given the impact of burns, it is essential to understand data on these patients. Methodology: This is an observational study based on data analysis available from the Information and Informatics Department of the Unified Health System (DATASUS) under the Ministry of Health (MS). The research included all municipalities in the state of Sergipe, using a sample consisting of all burn cases (ICD-T29) reported in Sergipe from 2019 to 2023. Results: In Sergipe, from 2019 to 2023, there were 966 hospitalizations due to burns. The year 2019 had the highest number of cases. October showed the highest number of burn cases, followed by November and September. A concentration of cases was noted in the state capital, Aracaju, and its surroundings. Regarding sex distribution, males were the most affected (62.52%). The most affected age group was 20-59 years (49.89%), followed by the pediatric age group (40.89%). During this period, the mortality rate was 4.3%, with a slight downward trend over the years.